PEMETAAN ZONA POTENSIAL RUKYAT HILAL DARI ROOFTOP GEDUNG MALL GTC MAKASSAR MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Hazimah, Nabila; Fatmawati, Fatmawati (Universitas Islam Negeri Alauddin Makassar, 2026)
Abstract The determination of crescent moon (hilal) observation sites is influenced not only by astronomical parameters but also by geographical aspects, particularly regional elevation conditions and the openness of the western horizon. This study aims to address the questions of how the potential zoning for hilal observation can be determined based on the elevation data of Makassar City and how the visibility characteristics of the western horizon from the rooftop of GTC Mall Makassar can be analyzed using a Geographic Information System (GIS) approach. This research employs a descriptive method with a quantitative approach based on spatial analysis using Digital Elevation Model (DEM) data, administrative boundary data from the Geospatial Information Agency (BIG), and the coordinate points of the rooftop of GTC Mall Makassar. The data were processed using ArcGIS through the stages of DEM extraction, elevation classification, spatial data overlay, and digital map visualization. The results indicate that Makassar City has an elevation range from -42 meters to 71 meters, which is classified into three zones: low elevation (-42–4 meters), medium elevation (4–12 meters), and high elevation (12–71 meters). Spatial analysis also reveals that the rooftop of GTC Mall Makassar is located within the low to medium elevation zones but has the potential to serve as a hilal observation site due to its geographical position in a coastal area, the openness of its western horizon directly facing the Makassar Strait, minimal topographical obstructions, and the additional observational height provided by the rooftop. Elevation is therefore not the sole factor in determining the potential of a hilal observation site but should be integrated with the openness of the western horizon and the characteristics of the observation location. The implications of this study indicate that the utilization of Geographic Information Systems can serve as a scientific, data driven approach to support the evaluation and selection of rukyat hilal observation sites in the future. Keywords: Geographic Information System (GIS), ArcGIS, Elevation, Western Horizon.